Tuning Magnetic Behavior of La₁₋ₓSrₓFeO₃ (x = 0.1–0.5) via Sr Doping: From Antiferromagnetism to Ferromagnetism - Ramlan; Naibaho, Marzuki; Ginting, Masno (Science and Technology Indonesia, 2026)
Strontium-substituted LaFeO₃ compounds with the chemical formula La₁₋ₓSrₓFeO₃ (x = 0.1–0.5) were successfully prepared via the solid-state reaction technique by partially replacing La at the A-site. Structural analysis was carried out using X-ray diffraction (XRD), while surface morphology and elemental composition were investigated by scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM–EDS). The magnetic behavior of the samples was evaluated using a vibrating sample magnetometer (VSM). XRD patterns confirmed that all synthesized compositions crystallized in a single-phase LaFeO₃ structure without detectable impurity phases. The dominant diffraction peak corresponded to the (121) crystallographic plane, indicating an orthorhombic structure with the Pnma space group (No. 62). SEM observations revealed irregular particle morphologies with a broad particle size distribution. EDS analysis verified the successful incorporation of Sr into the LaFeO₃ lattice, as evidenced by the presence of La, Fe, O, and Sr elements in all doped compositions (x = 0.1–0.5). Magnetic measurements showed that the La₀.₉Sr₀.₁FeO₃ sample exhibited the best magnetic performance, with a saturation magnetization (Mₛ) of 0.393 T and a coercive field (Hc) of 2661 Oe. The introduction of Sr induced a transition in magnetic behavior from antiferromagnetic to ferromagnetic ordering. Overall, these results demonstrate that La₁₋ₓSrₓFeO₃ materials are promising candidates for electromagnetic wave absorption applications.